A High Degree of LINE-1 Hypomethylation Is a Unique Feature of Early-Onset Colorectal Cancer - Antelo, Marina (2012)
Objective: Early-onset colorectal cancer (CRC) represents a clinically distinct form of CRC that is often associated with a poor prognosis. Methylation levels of genomic repeats such as LINE-1 elements have been recognized as independent factors for increased cancer-related mortality. The methylation status of LINE-1 elements in early-onset CRC has not been analyzed previously. Design: We analyzed 343 CRC tissues and 32 normal colonic mucosa samples, including 2 independent cohorts of CRC diagnosed ≤50 years old (n = 188), a group of sporadic CRC >50 years (MSS n = 89; MSI n = 46), and a group of Lynch syndrome CRCs (n = 20). Tumor mismatch repair protein expression, microsatellite instability status, LINE-1 and MLH1 methylation, somatic BRAF V600E mutation, and germline MUTYH mutations were evaluated. Results: Mean LINE-1 methylation levels (±SD) in the five study groups were early-onset CRC, 56.6% (8.6); sporadic MSI, 67.1% (5.5); sporadic MSS, 65.1% (6.3); Lynch syndrome, 66.3% (4.5) and normal mucosa, 76.5% (1.5). Early-onset CRC had significantly lower LINE-1 methylation than any other group (p<0.0001). Compared to patients with <65% LINE-1 methylation in tumors, those with ≥65% LINE-1 methylation had significantly better overall survival (p = 0.026, log rank test). Conclusions: LINE-1 hypomethylation constitutes a potentially important feature of early-onset CRC, and suggests a distinct molecular subtype. Further studies are needed to assess the potential of LINE-1 methylation status as a prognostic biomarker for young people with CRC.